Predictor Keberhasilan Pengobatan Tuberkulosis Tahun 2018 di Indonesia - riezky febiola; Mondastri Korib Sudaryo; Sri Ulfa Alriani (Universitas Ngudi Waluyo, 2020)
Tuberculosis is still a major cause of health problems and death due to infectious agents. The success rate of TB treatment varies globally where Asia is 81.6% the second highest after Oceania 83.9%. The prevalence of tuberculosis with bacteriological confirmation in Indonesia is 759 per 100,000 population. This study aims to determine the relationship between the independent variabel with the success of TB treatment in Indonesia in 2018. Methods This study was conducted using a retrospective cohort study design. The study population was all TB Drug Sensitive patients who started treatment in 2018 and were recorded on SITT. Data analysis was performed using Chi Square. 392,706 TB patients were included in the analysis of 476,744 patients. With treatment results 45.2% recovered, 43.35% complete treatment, 3% died, 0.8% failed, 5.6% dropped out of treatment, 2.1% people moved. Age> 45 years RR 1,028 (95% CI; 1,009-1,049), female gender 1,022 (95% CI; 1,004-1,041), HIV negative 1,229 (95% CI; 1,169-1,292), patients with new treatment status RR 1,072 (95% CI; 1.033-1.112) and did not have a DM RR comorbid 1.027 (95% CI; 1.003-1.051) were predictors of the success of TB treatment. The results of this study indicate that patients who do not have HIV or DM co-morbidities are more likely to succeed in TB treatment.